SARS-CoV-2 antibody trajectories after a single COVID-19 vaccination with and without prior infection - Jia Wei; Philippa C. Matthews; Nicole Stoesser; Ian Diamond; Ruth Studley; Emma Rourke; Duncan Cook; John I. Bell; John N. Newton; Jeremy Farrar; Alison Howarth; Brian D. Marsden; et al. (Nature Communications, 2022)
The impact of prior infection on the immune response to COVID-19 vaccination has not been fully characterised. Here, the authors use data from ~100,000 adults in the UK and find that a single vaccine dose in those with prior infection produces a comparable or stronger response to two doses in those without infection.